2014
DOI: 10.1002/jsfa.6955
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of catechin and extraction of active polysaccharide from green tea leaves via simultaneous treatment with tannase and pectinase

Abstract: Simultaneous processing with tannase and Rapidase can be an efficient method for the extraction of bioactive polysaccharides and biotransformation of catechins with enhanced radical scavenging activity from green tea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 41 publications
0
28
0
2
Order By: Relevance
“…The four major catechins in green tea extract include approximately 59% EGCG, 19% EGC, 13.6% ECG, and 6.4% EC [20], and green tea also contains GA and other phenolic acids, such as caffeic acid. Baik et al reported that the addition of green tea extract along with tannase treatment significantly increased the biotransformation of catechins, and pectinase-driven hydrolysis significantly increased interleukin-6 (IL-6) production in macrophages [21]. Dietary polyphenols, including EGCG, resveratrol, and curcumin are associated with the regulation of systemic inflammation and might relieve symptoms of muscle dysfunction [22].…”
Section: Discussionmentioning
confidence: 99%
“…The four major catechins in green tea extract include approximately 59% EGCG, 19% EGC, 13.6% ECG, and 6.4% EC [20], and green tea also contains GA and other phenolic acids, such as caffeic acid. Baik et al reported that the addition of green tea extract along with tannase treatment significantly increased the biotransformation of catechins, and pectinase-driven hydrolysis significantly increased interleukin-6 (IL-6) production in macrophages [21]. Dietary polyphenols, including EGCG, resveratrol, and curcumin are associated with the regulation of systemic inflammation and might relieve symptoms of muscle dysfunction [22].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for applications in which minimal loss of catechins is desirable, such as the production of GTE food supplements, enzymatic processing with CF is a preferable to acid hydrolysis for the production of flavonol aglycones from GTE. As increased GA content improves the radical scavenging effects of GTE [22], and beneficial dietary flavonols are best absorbed as aglycones [24], our research on the enzyme CF for producing flavonol aglycones from GT might potentially deliver useful information in processing application and beneficial advantage in human health.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the content of GA through the conversion of GTE by tannase has been shown to improve the radical scavenging activities of GTE [22]. Moreover, conversion of (-)-epigallocatechin gallate (EGCG) by tannase attenuated its toxicity without affecting the antiproliferative effects [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, through structural modification of EGCG, using specific polyunsaturated fatty acids such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), the physicochemical properties of EGCG have been modified, which has resulted in enhanced lipophilicity, so, these new compounds can be applied to products like marine oils (Figure ) (Zhong & Shahidi, ). In addition, enzymatic biotransformation of GTE, using tannase, has been shown to increase antioxidant activity of tea catechins (Baik et al., ; Hong et al., ; Macedo, Battestin, Ribeiro, & Macedo, ).…”
Section: Antioxidant Activity Of Egcgmentioning
confidence: 99%